2016
DOI: 10.1038/ncomms11897
|View full text |Cite
|
Sign up to set email alerts
|

Massive subsurface ice formed by refreezing of ice-shelf melt ponds

Abstract: Surface melt ponds form intermittently on several Antarctic ice shelves. Although implicated in ice-shelf break up, the consequences of such ponding for ice formation and ice-shelf structure have not been evaluated. Here we report the discovery of a massive subsurface ice layer, at least 16 km across, several kilometres long and tens of metres deep, located in an area of intense melting and intermittent ponding on Larsen C Ice Shelf, Antarctica. We combine borehole optical televiewer logging and radar measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
100
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 85 publications
(106 citation statements)
references
References 42 publications
6
100
0
Order By: Relevance
“…The occurrence of ice lensing within the firn has been observed in Cabinet Inlet, Larsen C by Hubbard et al (2016) and annual layers of high density were observed on Larsen C by Gourmelen et al (2009). Furthermore, the large features of solid ice observed by Hubbard et al (2016) suggest that significant saturation of the firn and refreezing of meltwater had previously occurred.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…The occurrence of ice lensing within the firn has been observed in Cabinet Inlet, Larsen C by Hubbard et al (2016) and annual layers of high density were observed on Larsen C by Gourmelen et al (2009). Furthermore, the large features of solid ice observed by Hubbard et al (2016) suggest that significant saturation of the firn and refreezing of meltwater had previously occurred.…”
mentioning
confidence: 94%
“…Furthermore, the large features of solid ice observed by Hubbard et al (2016) suggest that significant saturation of the firn and refreezing of meltwater had previously occurred.…”
mentioning
confidence: 99%
“…ground-penetrating radar, firn density modelling, and satellite images identified a massive subsurface body of anomalously warm and dense ice (Hubbard et al, 2016). This body of ice was interpreted to be the result of the intense melt and regular surface ponding that occurs in this area.…”
Section: Introductionmentioning
confidence: 99%
“…In late 2015 we drilled four boreholes in addition to that reported by Hubbard et al (2016), consisting of two directly downstream from Cabinet Inlet and two downstream from Whirlwind Inlet (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…In Cainet Inlet (Fig. 1), the firn contains a massive subsurface ice layer (Hubbard et al, 2016), influencing ice-shelf temperatures, density, and potentially, flow properties. The occurrence of föhn winds has increased in recent decades (Cape et al, 2015), contributing to the destabilization of Larsen B ice shelf through increased meltwater production.…”
Section: Introductionmentioning
confidence: 99%